PENINGKATAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA SISWA KELAS V SEKOLAH DASAR - Prastya, Dicky (Universitas Pendidikan Indonesia, 2017)
Abstract:. This research aims to improve the student learning output in science subject by utilizing cooperativemodel of student teams achievement division (STAD) type at the fifth class B of elementary school 1 Sidokerto district Bumiratu Nuban. This study was a classroom action research. The results showed that the type cooperative learning model student teams achievement division (STAD) can improve students' learning activities, judging from the average percentage of student learning activities in the first cycle of 77% and 85.5% the second cycle. The implementation of cooperative learning model type of student teams’ achievement division (STAD) may also increase the thoroughness of learning outcomes IPA. The percentage of students who complete the first cycle is 62.5% and the second cycle is 90.63% and an increase in the average score of N-Gain.Keywords: Learning Achievement, Cooperative STAD Abstrak: Penelitian ini bertujuan untuk meningkatan hasil belajar IPA pada siswa kelas VB SDN1 Sidokerto Kecamatan Bumiratu Nuban dengan menggunakan model pembelajaran cooperative tipe student teams achievement division (STAD).Penelitian ini termasuk dalam Penelitian Tindakan Kelas. Hasil penelitian menunjukkan bahwa model pembelajaran cooperative tipe student teams achievement division (STAD) dapat meningkatkan aktivitas belajar siswa, dilihat dari rata-rata persentase aktivitas belajar siswa pada siklus I sebesar 77% dan siklus II 85,5%. Penerapan model pembelajaran cooperative tipe student teams achievement division (STAD)juga dapat meningkatkan ketuntasan hasil belajar IPA. Persentase siswa yang tuntaspada siklus I sebesar 62,5% dan siklus II sebesar 90,63% dan terjadi peningkatan pada skor rata-rata N-Gain.Kata Kunci: Hasil Belajar, Cooperative tipe student teams achievement division (STAD).